DISTRIBUSI TEKANAN GAS PADA JARINGAN PIPA MENGGUNAKAN METODE HYBRID BROYDEN DAN ALGORITMA DIFFERENTIAL EVOLUTION - Setya Pratama, Choiryaldi
Consumer demands of natural gas as energy sources is expected to be increase. Gas distributor companies have to ensure gas distribution is going properly. Gas was distributed by pipeline network which consists of nodes that represent points of consumer, suppliers and junctions connected by pipe, valve and regulator. Assuming the gas flow is in steady-state and the system model consists of set non-linear continuous equations. The iterative method is widely used to solving non-linear equation system problem such as Newton and Broyden method. However, many iterative methods has a drawback which is depend on initial approximation in order to get convergence solution. Metaheuristic method such as Differential Evolution Algorithm is able to combined to get a close approximation solution that continue as initial approximation. Based on testing with both method Broyden and Hybrid using simple network pipelines has given good result that reached percentage of success is 100% form several tests. But, in using complex pipelines network problem the Hybrid method significantly has given better results than only use Broyden method of success percentage and convergence iteration total, respectively is 83.34% and 2732 iteration. Whereas, only using Broyden method has the results respectively is 60% and 3840 iteration.